IDENTIFIKASI BAKTERI Escherichia coli METODE MPN PADA AIR ISI ULANG DIPERUMNAS IV WAENA ABEPURA TAHUN 2021 - Fajar Bakti Kurniawan; Asrori Asrori; Yulianus Wina Krisna Alfreda (GEMA KESEHATAN, 2021)
Quality drinking water was assessed from microbiological parameters, is the absence of total coliform and Escherichia coli bacteria in 100 ml samples. The purpose was to identify Escherichia coli bacteria in refill drinking water produced by refill drinking water depot at Perumnas IV Waena Abepura. The research was conducted at the Laboratory of Microbiology, Health Polytechnic of the Ministry of Health in Jayapura. Water samples obtained from 6 depots. This type of research is descriptive. The quality of water bacteriology uses the Most Probable Number (MPN) method which consists of a presumptive test using 3 3 3 tube Lactose Broth (LB) media, and a Confirmation Test using Brillian Green Lactose Broth (BGLB) media, complete test using EMB agar. The results showed that at 6 water depots there were 3 negative samples or no Escherichia coli bacteria were found and 3 positive samples found Escherichia coli bacteria.